Enzymatic hydrolysis pretreatment combined with glycosylation for soybean protein isolate applying in dual-protein yogurt - Mengya Sun; Zhenhai Yu; Shuo Zhang; Caihua Liu; Zengwang Guo; Jing Xu; Guofang Zhang; Zhongjiang Wang (Food Chemistry: X)
This research investigated the viability of replacing milk protein with glycosylated soybean protein isolate (SPI) treated with different enzymatic hydrolysis times (0, 10, 20, 30, 40, and 50 min) in yogurt. The results showed that enzymatic hydrolysis pretreatment combined with glycosylation for SPI exhibited elevated grafting and solubility. Additionally, the high solubility of SPI (94.77 %) at 40 min facilitates the preparation of dual-protein yogurt (DPY). Compared to ESPI0-G, DPY that incorporates ESPI40-G through partial substitution of milk protein is capable of forming a denser and more stable gel matrix. Especially, the syneresis of DPY40 was reduced by 7.61 % compared to DPY0, which more closely approximates the texture properties of traditional yogurt. Meanwhile, glycosylated SPI treated with enzymatic hydrolysis can effectively degrade the beany flavor and slightly bitter taste in DPY. This study could provide a solid theoretical basis for the broader application and industrialization of plant-based yogurt.